PENGARUH MANAJEMEN PERPUSTAKAAN TERHADAP TINGKAT KUNJUNGAN SISWA DI MI AL-ISLAM JAMSAREN SURAKARTA TAHUN 2022/2023 - Rahmawati, Tiara Nur; Amin, Lailla Hidayatul; Rochmawan, Alfian Eko (Al’ulum Jurnal Pendidikan Islam, 2024)
The purpose of this study is to determine the influence of library management on the level of student visits at MI Al-Islam Jamsaren Surakarta in the academic year of 2022/2023. This type of research used a quantitative approach. The population in this study were all students of class I,II,III,IV,V,VI at MI al-Islam Jamsaren Surakarta, the sample was taken by random sampling. The data collection methods used questioneres and visits lists, while the data analysis technique used in this study used data mean, median mode, standard deviation, likert scale. The test used SPSS 22 and the hypothesis test used the product moment formula. Bassed on the result of research on student at the MI Al-Islam Jamsaren Surakarta library in 2022/2023, it shows that there is a an influence of library management on the level of student visits at MI Al-Islam Jamsaren Surakarta. By using the prerequisite in the kolmogorov-smirnov method normality test with a value sig. 0,052 > 0,05 and linearity using SPSS 22 with sig. 0,965 > 0,05.